Effect of Vineyard Location on Assyrtiko Grape Ripening in Santorini and Its Wine’s Characteristics - Aikaterini Karampatea; Eirini Vrentzou; Adriana Skendi; Elisavet Bouloumpasi (Biology and Life Sciences Forum, 2025)
Besides the other factors, the microclimate (terroir) influences the quality characteristics of wine. The Assyrtiko variety has adapted to the volcanic soil of Santorini but under climate change, finding an ideal location for full grape ripening represents a challenge in preserving the PDO quality of Santorini wines. Thus, this study aims to evaluate the effect of location and harvesting time on the quality of Assyrtiko wine. It assessed the location effect (three distant plots of land in three distant areas of the island) on the composition of grapes (water uptake, pH, sugar, and organic acid accumulation) during the ripening. The grapes were vinified using the same procedure. The aromatic volatile profile of the wines was evaluated with GC-MS. A two-way ANOVA revealed that besides location and harvest time, their interaction is also significant for the parameters studied, except for the interaction effect involving sugar content. The analysis of volatile aromatic compounds revealed that the wine from grapes harvested at a later date had a higher aromatic intensity with notes of citrus, white-fleshed, and tropical fruits. This wine surpasses the levels of 2-phenylethanol, isoamyl acetate, linalool, and 2-phenylethyl ester with 17.8%, 7.7%, 21.1%, and 15.6%, respectively, compared to the immediate next in descending order. Results suggest that the grape variety is better suited to the local climatic conditions when full grape ripeness is reached by the end of the growing season.